Linking transformational leadership, absorptive capacity, and corporate entrepreneurship - Imran Shafique; Masood Nawaz Kalyar (Administrative Sciences, 2018)
This study aims to analyze the nexus between transformational leadership and corporate entrepreneurship through an integration of dispersed scholarly work on transformational leadership, absorptive capacity, and corporate entrepreneurship under one framework. A survey method was employed for the collection of data from small and medium-sized enterprises (SMEs) of Pakistan. The data were analyzed using structural equation modeling (SEM) technique to empirically test the hypotheses. The results demonstrate that transformational leadership positively affects corporate entrepreneurship and its dimensions-namely, innovation, new business venturing, self-renewal, proactivity, and risk-taking-both directly and through absorptive capacity. The potential of transformational leadership to influence corporate entrepreneurship via absorptive capacity added additional interesting substitutes. Future studies may produce novel insights by examining different leadership styles, settings, or utilizing qualitative technique. Firms should invest to initiate transformational leadership training programs for their managers. Additionally, if these firms are aiming to promote corporate entrepreneurship, they should focus on hiring managers that have attributes of transformational leadership. Furthermore, they should also invest in absorptive capacity to utilize outside knowledge for the enhancement of entrepreneurial activities. This study exploits research work on the relationship between transformational leadership and corporate entrepreneurship in a novel way; it investigates the dimensions of entrepreneurship individually, as well as unidimensionally, and includes the mediating role of absorptive capacity and tests several other hypotheses that previously have been ignored. This study, compared to the existing research, contributes to the impact of transformational leadership on corporate entrepreneurship and absorptive capacity, especially in Pakistan's business settings.
Keywords: 350; transformational leadership; corporate entrepreneurship; absorptive capacity